Hyperthermophilic archaea produce membrane vesicles that can transfer DNA. Issue 1 (7th May 2012) - Gaudin, Marie; Gauliard, Emilie; Schouten, Stefan; Houel‐Renault, Ludivine; Lenormand, Pascal; Marguet, Evelyne; Forterre, Patrick
Summary Thermococcales are hyperthermophilic archaea found in deep‐sea hydrothermal vents. They have been recently reported to produce membrane vesicles (MVs) into their culture medium. Here, we have characterized the mode of production and determined the biochemical composition of MVs from two species of Thermococcales, Thermococcus gammatolerans and Thermococcus kodakaraensis. We observed that MVs are produced by a budding process from the cell membrane reminiscent of ectosome (microparticle) formation in eukaryotes. MVs and cell membranes from the same species have a similar protein and lipid composition, confirming that MVs are produced from cell membranes. The major protein present in cell membranes and MVs of both species is the oligopeptide binding protein OppA. This protein is also abundant in MVs from cells grown in minimal medium, suggesting that OppA could be involved in processes other than peptides scavenging. We have previously shown that MVs from Thermococcales harbour DNA and protect DNA against thermodegradation. Here, we show that T. kodakaraensis cells transformed with the shuttle plasmid pLC70 release MVs harbouring this plasmid. Notably, these MVs can be used to transfer pLC70 into plasmid‐free cells, suggesting that MVs could be involved in DNA transfer between cells at high temperature.